A diligência prévia do comprador na compra e venda imobiliária - Iaquinta, Rodrigo Ferrari (2024)
The aim of this academic paper is, based on a methodology of explanatory and bibliographical research, to carry out a specific analysis of the buyer's diligence in the purchase and sale of real estate. To this end, the first step is to analyze the structuring elements of the Brazilian real estate registry system, in order to analyze the general aspects and guiding principles of real estate registry activity. In addition, an analysis will be made of the effects of real estate registration, as well as considerations on the German and French systems of real estate registration. Next, central figures in the understanding of diligence from the perspective of the purchase and sale of real estate are addressed. Thus, the structuring elements of the purchase and sale of real estate are seen, and the legal nature of the duty of diligence is verified (whether it is an obligation, a duty per se or a burden). Once the legal nature of diligence has been verified, an analysis is made in the light of the Civil Law of Obligation, at which time the criterion of the good father of the family (bonus pater familias) and the figures of the average or normal man are discussed. Next, a brief historical overview of good faith is given and the defining elements of objective and subjective good faith are examined. Finally, in a third section, in order to contribute to a broad understanding of diligence in the purchase and sale of real estate, issues such as public faith in the registry, publicity in the real estate registry and the protection of appearance, the concentration of acts in the real estate registry and the current legal panorama on the subject are addressed